2014
DOI: 10.1080/09500782.2014.992905
|View full text |Cite
|
Sign up to set email alerts
|

The impact of video review on supervisory conferencing

Abstract: This study investigated how video-based observation may alter the nature of postobservation talk between supervisors and teacher candidates. Audio-recorded postobservation conversations were coded using a conversation analysis framework and interpreted through the lens of interactional sociology. Findings suggest that videobased observations impacted the content and extent of teacher candidate reflection during post-observation discussions, enabling candidates to comment at greater length about their teaching,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Afterward, this study examined the influence of video-based reflection to improve teaching skills. This study has a conclusively huge purpose of developing the teacher quality in the next teaching sessions which has similar objectives with the previous studies such as [4], [5], [16], which focus on developing teachers quality in the teaching process. Hence, it could credibly be assumed that video-based reflection assisted the teacher in developing the teaching quality.…”
Section: Observing In Multiple Timesmentioning
confidence: 76%
“…Afterward, this study examined the influence of video-based reflection to improve teaching skills. This study has a conclusively huge purpose of developing the teacher quality in the next teaching sessions which has similar objectives with the previous studies such as [4], [5], [16], which focus on developing teachers quality in the teaching process. Hence, it could credibly be assumed that video-based reflection assisted the teacher in developing the teaching quality.…”
Section: Observing In Multiple Timesmentioning
confidence: 76%
“…Indeed, video records of teaching have been used very successfully to support reflection in pre-and in-service teacher development (e.g., Baecher & McCormack, 2015;Rosaen, Lundeberg, Cooper, Fritzen, & Terpstra, 2008;Sherin & van Es, 2005;Tripp & Rich, 2012;Welsch & Devlin, 2007). These and many other studies have shown ways in which skilled facilitators enable teachers to reap the full benefits of video review.…”
Section: Laura Baecher and David Connormentioning
confidence: 95%
“…When considering the context of second language education, studies of preservice candidate beliefs have considered myriad issues, including: teacher educators who are not native speakers of the language (e.g., Kang, 2015); how they have been evaluated while in practicum (Merç, 2015;Baecher & McCormack, 2015); the discrete elements of the languages they are teaching (e.g., Fenwick, Humphrey, Quinn & Endicott, 2014); the methods of instruc-Teacher candidates in this study enter their Bachelor of Education (BEd) program with their own lived experiences as learners of a second language, either French, English, or even other languages. During their BEd year, they may add scientific concepts as gained through their methodology courses and additional concepts gained in practice teaching.…”
Section: L'influence De L'expérience Sur Le Système De Croyances D'unmentioning
confidence: 99%